Religious Differences in the Context of National and State Life Study of Hadith and Tafsir. - Sari Agustiani; Damanhuri (al-Afkar, Journal For Islamic Studies, 2024)
This research examines religious differences in the context of national and state life. Study of Hadith and Tafsir studies. The conclusions of this research are: First, it can be determined that all narrators have a degree of tsiqah in the hadith narrative by following their life history and assessing the quality of the hadith sanad which states protection for the ahlu dzimmah. In addition, the time span between each series of narrators is also the same. Thus, we can conclude that this hadith is shohihul sinad. Second, the hadith which talks about the Prophet SAW's defense of the ahlu dzimmah shows that the Prophet SAW's defense of the ahlu dzimmah was more than just a matter of accepting differences within the framework of the state; it also involves carrying out Allah's command in the Qur'an (QS Annahl verse 91) to keep promises. Apart from that, this shows that the hadith does not contradict the text of the Qur'an, making it an unequivocal shadz hadith. Therefore, it can also be concluded that this hadith is shohihul matni. Third, the Prophet SAW's recognition of the greeting of the Jews as narrated in the following hadith shows that socially the Prophet SAW was a figure who transparently acknowledged the existence of differences in everyday life. This is also followed by researchers in the resulting periods as shown in previous books.